Evaluasi Status Kesuburan Tanah Pada Lahan Pertanian di Kecamatan Denpasar Selatan - PINATIH, I DEWA AYU SRI PURNAMI; KUSMIYARTI, TATI BUDI; SUSILA, KETUT DHARMA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2016)
ABSTRACT Evaluation of Soil Fertility Status At Agriculture Land in South Of Denpasar District This study aims to evaluate the status of soil fertility in South Denpasar District. The method used in the research is soil sampling survey with started making land unit acquired by overlaying several thematic maps, then conducted some soil sampling individuals for each land unit who then composited. Soil samples have been obtained and analyzed in the laboratory analysis of soil chemical properties include: 1). Cation Exchange Capacity (CEC), 2). Base saturation (BS), 3). Soil Organic Matter, 4). Total Soil Phosphorus, 5).Total Soil Potasium. The results analysis of soil fertility status chemical characteristic are then clasified of soil fertility status based on Bogor Soil Research Center Prosedures (1995). The results showed that in South Denpasar District there are two classes of soil fertility status of medium fertility class (S) which includes land unit DS1 (Subak Renon, Intaran, Sidakarya, Wangbiga) , DS2 (Subak Suwung) , DS3 (Sanur Kauh) while high soil fertility is also found on the land unit DS1 sample DS1d . Two parameters of soil fertility which is the limiting factor is the low chriteria of soil organic matter status and total soil phosporus. Alternative of management land to address both the limiting factors are the addition of organic matters and phosphorus fertilization. Keywords: soil fertility status, South  of Denpasar district, agriculture land